A journey to a cold seep: How scientists study methane in the Arctic ocean: A paired teaching lesson plan - Mohadjer, Solmaz; Aune, Vibeke; Panieri, Giuliana; Oddone, Davide (Septentrio Educational, 2023)
Focus: Where are and what happens at cold seeps and how scientists study them. Learning objectives: After this lesson, students should be able to: • Relate different datasets by observing and describing scientific maps • Differentiate between carbon dioxide and methane gas • Clarify misconceptions about greenhouse gas • Explain what cold seeps are and why most gas/methane hydrates occur at continental margins • Describe some of the methods scientists use to locate and study methane/gas hydrates Prerequisites: Prior to this lesson, students should be familiar with understanding maps, molecular structure and bonding, and the greenhouse effect and gases. Key words: Arctic Ocean, Methane, Carbon Dioxide, Gas Hydrate, Cold Seep, Greenhouse Gases.